TOWARDS A GLOSSARY OF THE ETHIOPIAN ORTHODOX TÄWAḤƎDO CHURCH TRADITIONAL SCHOOLS: THE SCHOOL OF GƎʿƎZ POETRY (QƎNE BET) IN FOCUS - GebreMariam , Andualem Ermias (Journal of Oriental Studies, 2025)
The Ethiopian Orthodox Täwaḥǝdo Church (EOTC) is well known in its traditional schools that traces back to the Aksumite period, specifically following the introduction of Christianity. This article aims at exploring technical words and expressions used in the traditional schools of the Church, with a special focus on the School of Gǝʿǝz poetry, commonly known as ‘Qǝne Bet, ቅኔ፡ ቤት’. This school has played an indispensible role in the Ethiopian Christian literary treasures for centuries transmitting the knowledge of theology, poetry, exegesis, and linguistics, predominantly by means of oral literature. Qǝne Bet is the school where traditional students are supposed to be trained in composing their own poem, having practiced and recited some poetries composed by their teacher (the poet). The article comprises more than eighty technical terms and expressions collected from printed books, focus group discussions and personal experiences. These specialized words and phrases are used by Qǝne teachers (poets) and students in the teaching-learning process and/or during the ecclesiastical rites, and an entry is made for each term. As the traditional schools are likely to be deteriorated time and again, preserving the linguistic heritage of such glossaries, used in some other schools, and making them known to the scholastic world is very crucial, for several of them are merely transmitted orally. Keywords: Qǝne, terms, traditional school, conjugation, Gǝʿǝz poetry